Vibron-assisted spin excitation in a magnetically anisotropic molecule - Bachellier, N. (2020)
The electrical control and readout of molecular spin states are key for high-density storage. Expectations are that electrically-driven spin and vibrational excitations in a molecule should give rise to new conductance features in the presence of magnetic anisotropy, offering alternative routes to study and, ultimately, manipulate molecular magnetism. Here, we use inelastic electron tunneling spectroscopy to promote and detect the excited spin states of a prototypical molecule with magnetic anisotropy. We demonstrate the existence of a vibron-assisted spin excitation that can exceed in energy and in amplitude a simple excitation among spin states. This excitation, which can be quenched by structural changes in the magnetic molecule, is explained using first-principles calculations that include dynamical electronic correlations.